Pelaksanaan Peran Dinas Lingkungan Hidup Kota Payakumbuh dalam Pengendalian Pencemaran Air Sungai Batang Agam Kota Payakumbuh - Wulan Aulia Cikasimi; Jumiati Jumiati (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2023)
This research purposes to reveal the roles implementation, obstacles and efforts of the Payakumbuh City Environmental Service in controlling water pollution in the Batang Agam river, Payakumbuh City. This research used a method of descriptive qualitative and determined the research informants using purposive sampling. The researcher uses source triangulation techniques and technical triangulation which will then be analyzed. Based on the findings in the field, the researchers found that the Payakumbuh City Environment Service had facilitated, educated, interacted and coordinated, as well as carried out various technical activities in carrying out roles in controlling river water pollution in the Batang Agam Payakumbuh City. In the implementation of these activities found internal obstacles and external obstacles. The Payakumbuh City Environmental Service has made efforts to overcome these obstacles.